(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article presents the results of a study of the pulsations of the output current of a source intended to power DC traction motors, which ensures the rotation of the moving parts of wheel-motor units of electric locomotives and electric trains, with a frequency regulated for the position of in-place diagnostics of bearings. The experiments were performed in the MatLab/Simulink simulation environment. Graphic methods are used to determine the current pulsation coefficient of traction motors of electric rolling stock. Energy indicators were determined in tabular and analytical forms, as well as converter control parameters that ensure the standard value of the power factor. Based on the assessment, a circuit design for the source was proposed, including a three-phase uncontrolled bridge rectifier and a pulse converter.